Validating EEG source imaging using intracranial electrical stimulation - Unnwongse, Kanjana; Rampp, Stefan; Wehner, Tim; Kowoll, Annika; Parpaley, Yaroslav; Von Lehe, Marec; Lanfer, Benjamin; Rusiniak, Mateusz; Wolters, Carsten; Wellmer, Joerg (Brain Communications, 2022)
To evaluate the spatial accuracy of electrical source imaging (ESI) for known sources, Unnwongse et al. systematically performed ESI of averaged stimulation potentials recorded on simultaneous stereo-EEG and 37-electrode scalp EEG using individual finite element method models to determine the localization error.
CRIS-Team WoS Importer:2023-03-10